Myelination of the Postnatal Mouse Cochlear Nerve at the Peripheral-Central Nervous System Transitional Zone - Wang, Jue; Zhang, Baofu; Jiang, Hui; Zhang, Lei; Liu, Danzheng; Xiao, Xiao; Ma, Hannah; Luo, Xuemei; Bojrab II, Dennis; Hu, Zhengqing (Frontiers in Pediatrics, 2013)
In the nerve roots of vertebrates, the peripheral nervous system (PNS) and central nervous system (CNS) interface at the PNS-CNS transitional zone (PCTZ), which consists of cell boundaries with various myelin components. We have recently shown that the mouse cochlear nerve presents an exceptionally long segment of the CNS tissue extending into the PNS using light microscopy. However, it is unclear how oligodendrocytes and Schwann cells contribute to the formation of myelin components of the PCTZ. It is undetermined how myelination is initiated along the cochlear nerve, and when it adopts a mature pattern. In this study, immunofluorescence using antibodies specific to oligodendrocyte marker myelin oligodendrocyte glycoprotein (MOG) and Schwann cell marker myelin protein zero (MPZ) were used to detail the expression of myelin components along the postnatal mouse cochlear nerve. We found that the expression of MPZ was initially observed in the soma of bipolar spiral ganglion neurons at postnatal day 0 (P0) and progressed to the central and peripheral processes after P8–P10. Myelination of the CNS tissue was initiated in close proximity to the PCTZ from P7 to P8 and then extended centrally. Myelination of the PCTZ reached a mature style at P14, when the interface of the expression of MOG and MPZ was clearly identified along the cochlear nerve. This knowledge of PCTZ formation of the cochlear nerve will be essential to future myelination research, and it will also gain clinical interest because of its relevance to the degeneration and regeneration of the auditory pathway in hearing impairment.